Maktabgacha Yoshdagi Ta’lim-Tarbiya Berishning Zamonaviy Usullari - Saidov Ju’rat (Scholars Digest Publishing, 2023)
Educators have a great role in educating preschool children and in their development as adults in the future. Therefore, it is correct to say that the use of new modern methods in teaching children is the main factor in bringing up children in the spirit of the new age and making them mature professionals. In this article, you can consider the basis of these ideas.
Keywords: didactic games, mental ability, opportunities, conditions, Khoja Nasriddin.